The Use of Realistic Mathematics Education (RME) in Improving Mathematical Analogical Ability and Habits of Mind - Farida, Farida; Hartatiana, Hartatiana; Joemsittiprasert, Watcharin (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The purposesof this study are to see whether there are differences in mathematical analogical abilities between the class that was taught using Realistic Mathematics Education (RME) and class that was taught using expository learning, to see whether there are differences in mathematical analogical abilities of students who have high, medium, low habits of mind  taught using Realistic Mathematics Education Learning(RME), and to see whether there is an interaction between the use of Realistic Mathematics Education Learning( RME) on habits of mindand students' mathematical analogical abilities. This research is experimental, specifically thequasi-experimental design. The two-way ANOVA was used to analyze the data. Based on the results of the study, it can be concluded that: 1) there are differences in mathematical analogical abilities between the class that was taught using Realistic Mathematics Education (RME) and class that was taught using expository learning; 2) there are differences in mathematical analogical abilities of students who have high, medium, lowhabits of mind taught using Realistic Mathematics Education Learning(RME); 3) there is no interaction between the use of Realistic Mathematics Education Learning(RME)on the habits of mind and students' mathematical analogical abilities.